1994
DOI: 10.1007/bf02967374
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone-related protein in breast cancer tissues: Relationship between primary and metastatic sites

Abstract: The expression of parathyroid hormone-related protein (PTHrP) at primary and metastatic sites was studied retrospectively in specimens obtained at opreation and autopsy from 11 patients. The anti-human PTHrP monoclonal antibody, 4B3, was used in the immunohistochemical studies. The 11 cases showed metastases to the liver and the lung, and 9 showed bone metastases at autopsy. At primary sites, PTHrP was positive in the 9 cases with bone metastases, while the other 2 cases were negative for PTHrP. Regardless of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Initially, expression of PTHrP in the primary tumor appeared to be associated with formation of bone metastases [86,87]. In contrast, a large prospective study of 526 consecutive patients with operable breast cancer demonstrated that PTHrP expression in primary breast cancer was significantly associated with fewer (bone) metastases [84,[88][89][90]. Therefore, the most likely explanation for the observed increased PTHrP expression in breast cancer bone metastases [84,90], is that TGF-β in the bone microenvironment induces cancer cells to express PTHrP rather than cancer cells that metastasize to the bone having an intrinsically higher PTHrP expression.…”
Section: Tgf-β In Bone Metastasismentioning
confidence: 96%
“…Initially, expression of PTHrP in the primary tumor appeared to be associated with formation of bone metastases [86,87]. In contrast, a large prospective study of 526 consecutive patients with operable breast cancer demonstrated that PTHrP expression in primary breast cancer was significantly associated with fewer (bone) metastases [84,[88][89][90]. Therefore, the most likely explanation for the observed increased PTHrP expression in breast cancer bone metastases [84,90], is that TGF-β in the bone microenvironment induces cancer cells to express PTHrP rather than cancer cells that metastasize to the bone having an intrinsically higher PTHrP expression.…”
Section: Tgf-β In Bone Metastasismentioning
confidence: 96%
“…In other words, tumour-derived PTHrP acts as a circulating hormone like parathyroid hormone and induces hypercalcaemia. Recently, a series of studies has indicated that PTHrP is commonly expressed in breast cancer and that a higher expression of PTHrP may induce bone metastasis (Southby et al, 1990;Powell et al, 1991;Bundred et al, 1992;Vargus et al, 1992;Bouizar et al, 1993;Kohno et al, 1994a;Kohno et al, 1994b). It is conceivable that the PTHrP secreted by breast cancer cells, which exist in bone marrow, may act as a paracrine effector on osteoclasts, resulting in osteolytic involvement.…”
mentioning
confidence: 99%
“…In vitro studies have demonstrated that breast cancer cells alone have the capacity to degrade the bone matrix, although these lesions of bone or dentine slices are not of the magnitude of those resulting from osteoclast-mediated bone destruction (Eilon and Mundy, 1978). Studies have also shown that PTHrP is expressed by the metastatic breast cancer cells and is a critical component in the mechanism of breast cancer metastases to bone (Boyce et al, 1999;Chirgwin and Guise, 2000;de la Mata et al, 1995;Guise, 1997;Guise et al, 1993;Henderson et al, 2001;Kohno et al, 1994;Thomas et al, 1999;Uy et al, 1995;Uy et al, 1997;Yoshida et al, 2000). Co-culture experiments have shown that breast cancer cells can produce both PTHrP and M-CSF which induce RANKL mRNA levels and inhibit OPG mRNA levels in osteoblasts in vitro (Mancino et al, 2001;Thomas et al, 1999).…”
Section: Bodymentioning
confidence: 99%